(untitled) (Modern education and development, 2025)
The early detection of eye diseases plays a crucial role in preventing vision loss and improving treatment outcomes. With advancements in artificial intelligence (AI), particularly in machine learning and deep learning, it has become feasible to develop algorithms capable of identifying early signs of various eye conditions. This study presents an AI-based algorithm for detecting common eye diseases, such as diabetic retinopathy, glaucoma, and age-related macular degeneration (AMD). The proposed algorithm leverages convolutional neural networks (CNNs) to analyze medical imaging data, such as fundus photographs, optical coherence tomography (OCT), and visual field tests.